THE LEGAL MECHANISMS FOR ACHIEVING THE PROTECTION OF THE EMPLOYEES AGAINST COLLECTIVE DISMISSALS INTRODUCTION (Proceedings of the International Scientific Conference "Social Changes in the Global World", 2024)
Efforts to create a sustained labor legal system are quite present in our country, considering the number ofregulations that regulate the rights and obligations of employment, in the direction of the comprehensiveincorporation of numerous European standards into a system that will enable normal functioning in inaccordance with the constitutional norms. With the adoption of the Law on Labor Relations, the Republicof Macedonia has already created a legal basis for the construction of labor legislation such as is known inEuropean countries. The numerous amendments and additions to this Law, which are a consequence of theobligations undertaken from the signing of the Stabilization and Association Agreement, as well as from thenumerous international conventions and recommendations, mark a step closer to achieving the goal -creation of labor legislation according to European and international standards.When it comes to labor rights, the role of the International Labor Organization (ILO) must not and cannotbe overlooked, which, according to its Constitution and the Declaration on the Aims and Tasks of the ILO,has a single purpose and that is to improve living conditions and the foundations for lasting peace, whichcan be based solely on social justice. This goal can only be achieved through cooperation betweengovernment representatives, workers and employers. Regarding the rights of the employee and theobligations of the employer when it comes to the termination of the employment relationship by terminationof the employment contract for business reasons, two documents of the ILO are considered very significantand which are simultaneously transferred or transposed into our labor legislation, namely: the ConventionNo. 158, on the termination of the employment relationship at the initiative of the employer, 1983, andRecommendation No. 166 regarding the termination of the employment relationship at the initiative of theemployer.
Keywords: employment contract; collective agreement; the obligation to inform; business reasons